Lipopolysaccharide/endotoxin induces IL-18 via CD14 in human peripheral blood mononuclear cells in vitro - Manigold, Tobias; Böcker, Ulrich; Traber, Petra Sieglinde; Si, Tuan-Dong; Kurimoto, Masashi; Hanck, Christoph; Singer, Manfred V.; Rossol, Siegbert (Cytokine, 2000)
IL-18 shares activities with IL-12 in generating T-helper 1 cells and cytokine response. It mediates LPS/endotoxin lethality by IL-12 independent interferon-γ synthesis and it induces bacteria-related organ failure. As peripheral blood mononuclear cells (PBMC) are potent producers of IL-18, we studied the regulation of IL-18 upon exposure to LPS and Staphylococcus aureus (SAC) in vitro. Freshly isolated PBMC constitutively expressed IL-18 mRNA. After unstimulated preincubation for 48h, however, IL-18 transcripts were nearly not detectable by RT-PCR, but inducible by LPS or SAC (P<0.01). Both LPS and SAC were potent stimuli of IL-18 protein secretion (P<0.01). LPS-mediated IL-18 gene expression and secretion was CD14-dependent and significantly inhibited by co-incubation of PBMC with neutralizing CD14 antibody (P<0.01). We conclude that LPS-driven IL-18 is dependent on the expression of costimulatory factors and that IL-18 inhibition might attenuate IL-18-related toxic effects.